Ex Vivo Evaluation of Egg Yolk IgY Degradation in Chicken Gastrointestinal Tract - Wang, Huiwen; Zeng, Ximin; Lin, Jun (Frontiers in Immunology, 2021)
Egg yolk antibody (IgY), due to its unique features (e.g., cost-effectiveness for mass production), is emerging as a promising alternative to antibiotics to combat infectious diseases, particularly in livestock. Oral administration of egg yolk IgY is the most common and convenient route that has been extensively investigated for controlling enteric pathogens. However, in vivo stability of egg yolk IgY in gastrointestinal (GI) tract, a critical issue for the success of this approach, still has not been clearly elucidated. Our recent study showed instability of orally administered egg yolk IgY in chicken GI tract, as demonstrated by both in vivo and ex vivo evidence. To better understand the magnitude and dynamics of instability of egg yolk IgY in vivo, in this study, we conducted comprehensive ex vivo analyses by spiking hyperimmune egg yolk IgY in fresh GI contents collected from five broilers at each sampling age (2, 4, or 6 weeks). The pH in gizzard slightly increased with age from 2.4 to 3.0. ELISA analysis indicated that a short time of treatment (30 or 60 min) of IgY with the gizzard contents from the chickens at 2, 4 and 6 weeks of age greatly reduced specific IgY titer by over 8, 6, and 5 log2 units, respectively, when compared to saline control. However, small intestine content only had a mild effect on egg yolk IgY, leading to 1 log2 unit of reduction in IgY titer upon 30 min of treatment. Consistent with these findings, SDS-PAGE and immunoblotting analyses provided direct evidence demonstrating that egg yolk IgY could be drastically degraded to undetectable level in gizzard content upon as short as 5 min of treatment; however, the IgY was only slightly degraded in small intestine content. Immunoblotting also showed that treatment of IgY with HCl (pH 3.0) for 60 min did not affect its integrity at all, further supporting the enzymatic degradation of IgY in gizzard. Collectively, egg yolk IgY could be substantially degraded in chicken gizzard, highly warranting development of effective approaches, such as encapsulation, for the controlled release and protection of orally administered egg yolk IgY in livestock.